PENERAPAN STRATEGI PEMBELAJARAN QUESTION STUDENT HAVE (QSH) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII3 SMP NEGERI I RIMBA MELINTANG TAHUN PELAJARAN 2011/2012 - Yustini Yusuf; Yustina '; Enik Suryati (Program Studi Pendidikan Biologi, 2012)
Direction of this research to increase motivation and biology of student class VIII3 SMPN 1 Rimba Melintang by study method of QSH. This research is class attacted was carried out on November until Desember 2011. The subject of this research are students class VIII3 SMP N 1 Rimba Melintang with total students is 37 persons, which compound at 14 male and 23 female. Parameter this research is study of motivation, evaluation students and teacher activity. The mean of motivation before class attacted by cycle I were 3,11 (medium category), and after class attacted by cycle increase to 3,65 (medium category) with 17,36% of persentase, then in the cycle II, motivation score increase to 3,95% (high category), with 27,01% of persentase. Reserve capacity students increased in cycle I with mean 70,54 (sufficient category), and cycle II with mean 77,70 (good category). The study completable of student increase to 83,78% in sycle I and 94,59% in cycle II. Student activity were increase from 73,98 (sufficient category) in cycle I to 84,46 (good category) in sycle II. And the teacher activity were crease from 95% (good) in sycle I to 100% (the best) in sycle II. The conclution of this research are using method QSH in process study can increase motivation and evaluation study of biology student class VIII3 SMP N 1 Rimba Melintang years lesson 2011/2012Keywords : Evaluation, Method QSH, Study motivation